(untitled) (International relations and international law Journal, 2018)
The main purpose of this article is to point the challenges, threats and risks, both internal and external in nature, that affect the stability of current political regimes in the region. Events in Ukraine remain a relevant topic for all five Central Asian countries. The defragmentation of Ukraine could become a negative precedent for Uzbekistan, Tajikistan, and Kyrgyzstan, as there are unresolved border disputes between these three countries. To study these questions authors have used transitological theories to analyze the internal policies of Central Asian countries. The theory of globalization, regionalization and interdependence helps in understanding the ongoing processes in Ukraine that could have an effect on the stability of political regimes in Central Asia. Key words: Central Asia, Ukraine, crisis, stability, destabilization.